A Study of Some Bacteria Affecting Urinary Tract of Children with Renal Disease - Eman Abbas Muhsin; Rajwa H. Essa; Sinaa M. Shakir (Journal of Madenat Alelem University College, 2013)
This study was carried out between December 17, 2008 and August 25, 2009. It included 62 pediatric patients at the age range (1-12) years of both genders: 26 with chronic renal failure (CRF) and 36 with nephritic syndrome (NS), who were outpatients and in-patients in the dialysis unit in both Al-Mansour pediatric teaching hospital and Child’s central teaching hospital. The control group consisted of 26 children. Urine and blood samples were collected from children with both renal diseases and healthy controls. Renal function was evaluated by biochemical tests of blood. After culturing the urine samples on both MacConkey agar medium and blood agar medium, general urine examination (GUE) was applied regardless the type of the renal disease. Results explained significant increase in both urea and creatinine concentrations in serum (P<0.001). General urine examination of both CRF and NS patients showed that casts presence in urine was not significant (p=0.056), while albuminuria was significant (P=0.049). The negative urine cultures were present in 64.5% of both patients’ groups. The control group showed no bacteria in urine. The positive cultures in patients (35.5%) were indicating urinary tract infections (UTIs) with a significant relation with the type of renal disease (P=0.042). UTIs seemed to be related with gender (P=0.044). The bacterial growth included the following isolates: E. coli (54.55%), Pseudomonas aeruginosa (22.73%), Klebsiella pneumoniae (9.09%), Proteus mirabilis (9.09%) and Morganella morganii in one case only (4.55%). The bacterial isolates were different in their sensitivity to antibiotics, which included Ceftazidime, Cefteriaxone, Gentamycin, Nalidixic acid, Nitrofurantoin and Trimethoprime).